Batik Santri: Training, Education, and the Creative Economy Potential of Islamic Boarding School–Based Initiatives in Kudus Regency - Sugiarto, Eko; Fiyanto, Arif; Retnoningrum Hidayah; Anung Gunarto; Achmad Zairin; Muhammad Rijalul Azka Arifin (Universitas Negeri Semarang, 2025)
Islamic boarding schools (pesantren) possess strategic potential for advancing the creative economy grounded in cultural and community-based resources, particularly through the batik industry. Pondok Pesantren Al-Mawaddah in Kudus Regency has established a batik business unit since 2018 as part of its pesantren entrepreneur program; however, it has not yet demonstrated optimal competitiveness. This study aims to develop a model for strengthening the pesantren-based creative economy through entrepreneurship training, eco-religious–based santri batik product innovation, and digital branding strategies. This study employs an action research approach encompassing the stages of planning, action, observation, and reflection. Data were collected through participatory observation, interviews, and documentation, and analyzed using descriptive qualitative methods. The findings indicate that (1) pesantren possess strong human resource potential for batik industry development, (2) entrepreneurship training and education enhance the technical and managerial competencies of santri, (3) eco-ethnic and eco-religious–based santri batik product innovation generates a distinctive product identity, (4) santri-preneur competencies improve in the domains of production, entrepreneurship, and digital marketing, and (5) digital branding strategies expand market reach and strengthen the position of santri batik within the creative economy ecosystem. This study affirms the strategic role of pesantren as centers for culturally grounded creative economy development and proposes an integrative model for strengthening santri entrepreneurship through education, training, product innovation, and digital branding.